The road to green development: How can carbon emission trading pilot policy contribute to carbon peak attainment and neutrality? Evidence from China - Lan, Junshi; Li, Wenli; Zhu, Xinwu (Frontiers in Psychology, 2022)
Carbon emissions trading is not only a market-based instrument but also one of the government's macro policies, which is extremely crucial to fulfilling both carbon peak attainment and carbon neutrality goals. For this purpose, this paper adopts a 30-region dataset for the period from 2008 to 2020 in China and employs the Differences-in-Differences (DID) method to quantify the effect of the carbon emissions trading pilot policy (CETP) on carbon emissions on the basis of introducing industrial structure upgrading and green technology innovation as moderating variables. The results show that (1) CETP has a statistically significant dampening effect on carbon emissions, while its carbon emission reduction effect follows a significant strengthening trend as the policy year of CETP implementation is delayed. (2) CETP has a significant carbon emission reduction effect. However, its effect demonstrates a gradual decrease from the eastern to the central and finally to the western regions. (3) CETP can inhibit carbon emissions depending on industrial structure upgrading to a certain extent, and this dependence is significant in the national and eastern regions but not in the central and western regions. (4) CETP's carbon emission reduction effect is dependent on green technology innovation, which is only revealed in the western region and performs as a dampening effect in the national and eastern and central regions, but not significantly.